[Image 06] - Smith, Captain Sir William [?ob. 1732] (My University, 1807)
Captain Sir William Smith was in the Royal Engineers.
Original drawings and paintings of Ireland and Scotland, vol 1
View of the Ruins of an Old Castle or Fortification and past the town and county at Newtown Stewart drawn by Sir. Wm Smith in 1807.
Keywords: Newtown Stewart; Fortification; Architectural drawings; Ireland -- Antiquities -- Pictorial works; Tyrone (Northern Ireland) -- Pictorial works; Castles in art; Landscapes (Representations) 1800-1810